2016
DOI: 10.1158/0008-5472.can-16-0868
|View full text |Cite
|
Sign up to set email alerts
|

The Biodistribution and Immune Suppressive Effects of Breast Cancer–Derived Exosomes

Abstract: Small membranous secretions from tumor cells, termed exosomes, contribute significantly to intercellular communication and subsequent reprogramming of the tumor microenvironment. Here, we use optical imaging to determine that exogenously administered fluorescently labeled exosomes derived from highly metastatic murine breast cancer cells distributed predominantly to the lung of syngeneic mice, a frequent site of breast cancer metastasis. At the sites of accumulation, exosomes were taken up by CD45 bone marrow-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
236
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(244 citation statements)
references
References 49 publications
7
236
1
Order By: Relevance
“…Currently, the original research information on the biodistribution of EVs is extraordinarily scarce [83,84,85]. The use of clinically approved radioisotopes for labeling EVs seems a fruitful approach.…”
Section: Manufacturingmentioning
confidence: 99%
“…Currently, the original research information on the biodistribution of EVs is extraordinarily scarce [83,84,85]. The use of clinically approved radioisotopes for labeling EVs seems a fruitful approach.…”
Section: Manufacturingmentioning
confidence: 99%
“…Exosome derived tumor cells are called Tumor-Derived (TD) exosomes and accumulating evidence suggest that TD exosomes can construct a suitable TME to support tumor proliferation, angiogenesis, invasion and metastasis (Bobrie et al, 2012; Cho et al, 2012; King et al, 2012; Luga et al, 2012) through exosome mediated signaling. Breast cancer-derived exosomes can directly suppress T-cell proliferation and inhibit NK cell cytotoxicity, and thereby suppress the anticancer immune response in premetastatic organs (Wen et al, 2016). Studies show that the small GTPases RAB27A and RAB27B regulate exocytosis of multivesicular endosomes, which lead to exosome secretion, in human HeLa cells.…”
Section: Tumor Cell Interactions With the Mesenchymementioning
confidence: 99%
“…It has also been reported that exosomes, along with cytokines and other soluble mediators, are involved in the transport of bone marrow‐derived cells to a premetastatic niche to enable the establishment of a tumor microenvironment . Furthermore, exosomes were also found to maintain a role in tumor survival via allowing the tumors to design an immune‐escape mechanism …”
Section: Exosome Functionsmentioning
confidence: 99%